Invited Commentary: A Matter of Survival—The Detrimental Consequences of Adverse Early-Life Conditions. Issue 10 (5th May 2018) - de Rooij, Susanne R
Abstract: Studies across different species have shown that moderate dietary restriction is associated with a longer life span. Surprisingly, however, when diet is restricted in prenatal life, the effect is completely the opposite. Animal studies and human epidemiologic data have shown that undernutrition in utero negatively affects health in later life and reduces life span considerably. In this issue of the Journal, Schoeps et al. ( Am J Epidemiol . 2018;187(10):2085–2092) provide new evidence that variations in nutritional conditions during pregnancy relate to the future health of the unborn child. In a detailed analysis of data from Muslim and non-Muslim pregnant women in Burkina Faso, they showed that the occurrence of Ramadan in early life was strongly associated with mortality rates among children under 5 years of age. Mortality rates were highest when Ramadan had occurred in the preconception period or during the first trimester. That nutritional conditions in early life can have such profound consequences for child mortality is both astonishing and extremely relevant from a public health perspective.